1997
DOI: 10.1128/jcm.35.11.2943-2948.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of Candida species in experimentally infected tissue and human blood by rRNA-specific fluorescent in situ hybridization

Abstract: Two 18S rRNA-targeted oligonucleotide probes specific for Candida albicans and Candida parapsilosis were used to detect and identify by fluorescent in situ hybridization these medically important Candida species in deep organs of mice after experimental systemic infection. The C. albicans-specific probe detected fungal cells in kidney, spleen, and brain sections of a mouse infected with C. albicans but not in a mouse infected with the closely related species C. parapsilosis. Conversely, the C. parapsilosis-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Therefore, we used a simple hypotonic ⁄ detergent (H ⁄ D) lysis step (0AE1% Triton X-100 in distilled water, as described in Materials and methods) to quickly remove intact red blood cells from the system prior to fixation, hybridization and analysis. Similar approaches taking advantage of the differential lability of red blood cells and yeasts have been reported previously (Jones 1990;Lischewski et al 1997;Kempf et al 2005). Figure 3, panel B, provides an overlay-based comparison of C. albicans populations recovered from blood using the H ⁄ D lysis approach and hybridized with two different probe treatments.…”
Section: Use Of Calb-1249 Cocktail For Detection Of Candida Albicans mentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, we used a simple hypotonic ⁄ detergent (H ⁄ D) lysis step (0AE1% Triton X-100 in distilled water, as described in Materials and methods) to quickly remove intact red blood cells from the system prior to fixation, hybridization and analysis. Similar approaches taking advantage of the differential lability of red blood cells and yeasts have been reported previously (Jones 1990;Lischewski et al 1997;Kempf et al 2005). Figure 3, panel B, provides an overlay-based comparison of C. albicans populations recovered from blood using the H ⁄ D lysis approach and hybridized with two different probe treatments.…”
Section: Use Of Calb-1249 Cocktail For Detection Of Candida Albicans mentioning
confidence: 82%
“…2). As noted in Results, a simple hypotonic ⁄ detergent lysis step similar to pre-analytical approaches used by other groups (Jones 1990;Lischewski et al 1997;Kempf et al 2005) was used to remove potentially interfering red blood cells from the sample prior to fixation and hybridization. Removal of red blood cells was an essential step, as their clumping interfered with yeast detection via flow cytometry (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…119 This technique has been reported for the identification of Candida spp. 131,132 and Aspergillus spp. 133,134 Although the entire procedure is rapid and easy to perform, the sensitivity of the assay is often lower than those of other molecular biological assays, especially those including nucleic acid amplification.…”
Section: Dna Basedmentioning
confidence: 99%
“…4,7-9 However, only a few studies have investigated FISH assays for other clinical samples such as infected tissue and human blood. 11 This study focused on optimising the hybridisation parameters for different types of clinical samples, facilitating the detection and identification of Candida species in different samples. In this study, we showed that only minor adjustments in the fixation and hybridisation time are necessary to make the protocol applicable for different samples.…”
Section: Discussionmentioning
confidence: 99%